Before the poison - Robinson, Peter, 1950- (New York : William Morrow, 2012)
Chris, a Hollywood music composer, returns to Yorkshire Dale to keep a promise to his dead wife. He rents a house, and is distracted by the murder that happened in the house sixty years ago.
A Chief Inpector Banks novel.
Keywords: Banks, Alan (Fictitious character) -- Fiction; Police -- England -- Yorkshire -- Fiction; Murder -- Investigation -- Fiction; Composers -- Fiction; Widowers -- Fiction; Guilt -- Fiction; Euthanasia -- Fiction; Yorkshire Dales (England) -- Fiction; Yorkshire (England) -- Fiction